Effect of Osmotic Stress on the Growth, Development and Pathogenicity of Setosphaeria turcica - Liu, Yuwei; Gong, Xiaodong; Li, Moxiao; Si, Helong; Zhou, Qihui; Liu, Xingchen; Fan, Yu; Zhang, Xiaoyu; Han, Jianmin; Gu, Shouqin; Dong, Jingao (Frontiers in Microbiology, 2021)
Osmotic stress is a severe condition frequently encountered by microorganisms; however, there is limited knowledge on the influence of hyperosmotic stress on the growth, development and pathogenicity of phytopathogenic fungi. Here, three osmotic conditions (0.4 M NaCl, 0.4 M KCl, and 0.6 M sorbitol supplemented in potato dextrose agar medium) were used to identify the effect of osmotic stress on the growth, development and pathogenicity of Setosphaeria turcica which is a plant pathogenic fungus and causes northern corn leaf blight disease in maize, sorghum, and related grasses. In osmotic stress, the growth rate of mycelium was decreased, and the number of vesicular structures and flocculent secretion outside the hypha cell wall were significantly increased. The qRT-PCR results showed that the osmotic stress quickly activated the HOG-MAPK pathway, up-regulated the expression of the downstream genes, and these genes were most highly expressed within 30 min of exposure to osmotic stress. Furthermore, the germination rate and the yield of conidia were significantly higher under osmotic stress than in the control. A pathogenicity analysis confirmed that pathogenicity of the conidia which were cultured under osmotic stress was significantly enhanced. By analyzing the knock-out mutants of an osmotic stress responsed gene StFPS1, an aquaglyceroporin downstream of the HOG-MAPK pathway, we found that StFPS1 was involved in the formation of appressorium and penetration peg, which affected the penetration ability of S. turcica. In summary, our work explained the correlation between osmotic stress and growth, development, and pathogenicity in S. turcica.